Rightsizing Satuan Polisis Pamong Praja; Studi Kasus Kota Lubuk Linggau 2012 - Suripto, Suripto; Faozan, Haris (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
Lubuklinggau city's economic growth in 2012 is quite high relative directly or indirectly increasing urban population. In addition to the positive side, the urban as well as the growing negative impact of street children, street vendors, illegal immigrants, and so on. The condition can affect to the increasing workload of Civil Service Police Unit (municipal police) Lubuklinggau City. Taking into account the increased workload and Government Regulation (PP) No. 6 In 2010, the municipal police peint done rightsizing. How rightsizing Lubuklinggau City municipal police are professional, effective and efficient? Rightsizing is needed to improve the quality and service to the community needs to be better and more efficient. Selanjuntya to answer that question this study uses descriptive evaluative methods and semi-exploratory. The analysis shows that the city municipal police Litbuklinggau feasible arrangement with the organization in accordance with the Type A No. Permendagri. 40 in 2011. Kelayakkan is also supported by the Office of the real condition of the municipal police workload is increasing from year to knowledge, especially in the field of public law enforcement and community protection.